Do odour impact criteria of different jurisdictions ensure analogous separation distances for an equivalent level of protection?. (15th June 2019) - Brancher, Marlon; Piringer, Martin; Grauer, Andreas F.; Schauberger, Günther
Abstract: Governments are increasingly introducing odour impact criteria (OIC) to determine separation distances between odour sources and residential areas. Previous studies have shown the wide range of OIC available for this purpose, depending on the desired level of protection against odour annoyance. However, it is unclear whether OIC with similar levels of protection can ensure analogous separation distances, which would reasonably be expected. This study presents a comparative analysis of separation distances calculated at two sites for different OIC, but all related to an equivalent level of protection. Here, the equivalent level of protection was defined for urban residential areas (land use), swine odour (hedonic tone) and new facilities (facility type). In this manner, the regulatory criteria currently enforced in Germany, Ireland, and Queensland (Australia) were selected as references for the investigation. The results clearly show that, even for an equivalent level of protection, disparate separation distances can be obtained. Differences in separation distances were found to be greater in prevailing wind directions compared to distances in additional wind directions. Overall, the results demonstrate a risk of poor conclusions in odour assessments. This means that care must be taken when adopting OIC for decision making, principally in those countries that have not yet established specific regulations to manage environmental odours. Concomitantly, the results stress the need for better harmonisation of the concept of the odour impact criterion and components thereof. By using perturbation analysis, it has also been found that the stack exit temperature influences the separation distances in a distinct way, reliant on the criteria used to determine the distances. This finding is of significance for input data collection in future odour modelling studies. Furthermore, approaches used to derive OIC, equivalence between dispersion modelling and field inspections (European standard EN 16841-1), as well as implications of the findings for regulatory practice are summarised and discussed. Graphical abstract: Image 1 Highlights: Distances from odour sources to receptors can be enforced to tackle odour annoyance. Separation distances were determined for country-specific odour impact criteria. Dissimilar distances were found even by relating the criteria to an equivalent level of protection. The stack exit temperature was identified as a relevant predictor for the separation distance. The findings of this work can support policymakers in designing odour regulations.